A Study of the Effect of the Use of Magnetised Water Technology to Increase the Hatching Rate of Common Carp (Cyprinuscarpio) in Hatching Incubators - Abdulhusein Hamzah Jawdhari (Journal of Global Pharma Technology, 2018)
This study was conducted in the fish hatchery of the Middle Euphrates Fish Production Company in Babylon Governorate on 1/4/2017 and used in three different strengths of magnetised water, known as tensile (700, 1400. 200) gauss, respectively, for five days, using four glass incubators (Zucker). The fertilised fish eggs were placed in four treatments with 100 g in each incubator. 1-2-3-4 The first incubator contained normal non-magnetised water. The second buffer was highly magnetised water 700, the third was 1400, and the fourth was 2000 gauss. Measure Percentage of oxygen, Electrical conduction, and Salinity by using a device YIS (conductivity meter) and Use the mercurial thermometer to measure the temperature. Was noticed that the incubator exposed to an intensity of 1400 gauss increased the proportion of oxygen in it and reached 10 while the lack of electrical conduction rate reached 40 and achieved a hatch rate 90% higher than those of the other treatments, with the hatching time beginning about8 hours before the others.Keywords: Magnetised Water, Hatching, Fish eggs, Magnetism intensity.